ANALISA HIRDOLIS PADA JARINGAN TRANSMISI AIR BERSIH SPAM BONLEU KECAMATAN TOBU, KABUPATEN TIMOR TENGAH SELATAN - Neka, Marianus Andre; Pattiraja, Agustinus Haryanto; Manubulu, Chstiani Chandra (Program Studi Teknik Sipil Universitas Katolik Widya Mandira, 2024)
Water is a basic need for human life, where its availability and optimal distribution play an important role in improving people's welfare. One of the water sources that is commonly used is groundwater. Based on data from the Central Statistics Agency of East Nusa Tenggara in 2018, there are 2,576 groundwater springs in the province, with 666 of them in South Central Timor Regency. However, challenges in the clean water distribution system, such as limited access and difficult geographical conditions, often hinder the fulfillment of water needs for the community. This study aims to analyze the hydraulic conditions of the clean water transmission network at SPAM Bonleu, Tobu District, South Central Timor Regency. The research methods include literature studies, data collection through field studies, data processing using AutoCAD Civil 3D, EPACAD, and EPANET V2.0 software, as well as hydraulic analysis of pressure, flow velocity, and head loss in the transmission network. The modeling results show that the pressure in the network is greater than the required standard, which is more than 250 m of water column. The flow velocity meets the minimum standard of 0.3 m/s, while the head loss is within the permitted limit, which is not less than 10 m/km. However, there is one parameter that does not meet the requirements, so further evaluation is needed for system optimization